Comparing the drivers of sustainable procurement for environmentally sensitive construction: global insights and evidence from Africa - Kuruneri, Joseph; Dube, Muneinashe; Chibaro, Munyaradzi; Moabi, Omponye; Obadire, Ayodeji Michael (Frontiers in Sustainability, 2026)
Sustainable procurement has emerged as a key source of competitive advantage in the highly competitive construction sector, compelling industry players to be more mindful of the environmental impacts of their decisions and activities. This study compares the drivers of sustainable procurement for environmentally sensitive construction in both global and African contexts. Guided by PRISMA, the study systematically reviews prior research to examine these drivers. A total of 34 studies published between 2010 and 2025 were reviewed, identifying nine major factors that influence sustainable procurement (SP) from stakeholder, institutional, and resource-based perspectives. Institutional drivers include regulations and policies, professional bodies, and benchmarking. Resource-related drivers include cutting-edge technology, organizational culture, supply chain capabilities, and human resource capacity. Stakeholder-related drivers comprise government and client requirements, non-governmental organizations, and supply chain collaboration. In contrast to global contexts, African research demonstrated minimal enforcement and limited mimetic adoption; however, regulatory pressure emerged as the most common and influential driver. With only six African studies identified, the analysis reveals a significant geographic gap and offers a novel theoretical synthesis, underscoring the need for more substantive evidence on SP in the African construction industry. Although the study complemented Scopus-indexed articles with a snowballing strategy to enhance depth, it may still have overlooked relevant studies, particularly gray literature a limitation that is especially notable in the African context, where social procurement research remains in its infancy. Additionally, future studies could apply meta-analysis to quantify the exact influence of each driver, as the current study is qualitative.